THỰC TRẠNG SỬ DỤNG KHÁNG SINH DỰ PHÒNG TRONG PHẪU THUẬT SẠCH, SẠCH NHIỄM VÀ MỘT SỐ YẾU TỐ ẢNH HƯỞNG TẠI TRUNG TÂM Y TẾ KHU VỰC TÂN SƠN GIAI ĐOẠN 2024–2025 (Vietnam Journal of Community Medicine, 2026)
1)Objective: This study aimed to describe the current status of prophylactic antibiotic use in clean and clean-contaminated surgeries and to explore factors influencing its implementation at Tan Son Regional Medical Center during the period 2024–2025.2)Methods: A sequential explanatory mixed-methods design combining quantitative and qualitative approaches was employed. The quantitative component reviewed 160 medical records of patients undergoing clean and clean-contaminated surgeries at the Department of General and Specialized Surgery and the Department of Obstetrics and Gynecology – Reproductive Health Care. The qualitative component consisted of five in-depth interviews and two focus group discussions conducted with managers and healthcare workers.3)Results: The proportion of prophylactic antibiotic use fully compliant with all five criteria was very low, accounting for 8.1%. In the Department of General and Specialized Surgery, compliance with prophylactic antibiotic guidelines was 38.5%, while non-compliance accounted for 61.5%. In the Department of Obstetrics and Gynecology – Reproductive Health Care, the compliance and non-compliance rates were 91.8% and 8.2%, respectively. Overall compliance with prophylactic antibiotic guidelines was 83.1%, whereas the non-compliance rate was 16.9%.Several facilitating factors for prophylactic antibiotic use were identified, including the implementation of internal guidelines, improved knowledge among physicians and nurses through professional training sessions, and upgraded information technology systems. However, several barriers remained. A small proportion of physicians lacked confidence in the effectiveness of prophylactic antibiotics and were concerned about the risk of surgical site infections if prolonged postoperative therapeutic antibiotics were not prescribed. In addition, microbiological surveillance activities conducted by the infection control department remained limited, with insufficient scientific evidence available to support clinical practice. Patient-related factors were also found to influence the utilization of prophylactic antibiotics.4)Conclusion: The rate of prophylactic antibiotic use in clean and clean-contaminated surgeries remained lower than recommended. Standardization of procedures, enhanced training, and strengthened supervision are necessary to improve the effectiveness of prophylactic antibiotic use in surgery. Misconceptions among patients should also be incorporated into Patient Council meeting discussions to improve awareness and facilitate experience-sharing for future practice.
Keywords: prophylactic antibiotics, clean surgery, clean-contaminated surgery, influencing factors.